2016
DOI: 10.5603/gp.2016.0075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic causes of recurrent miscarriages

Abstract: Recurrent miscarriage is an important problem in reproductive health, which affects 1-5% of couples. The aim of this article is to summarize current knowledge on the genetic causes of recurrent miscarriage. It presents the most common parental genetic disorders (karyotype abnormalities, recessive diseases carrier status, dominant diseases and thrombophilia) connected with recurrent pregnancy loss, as well as research into other possible genetic causes. This review also sets out to demonstrate changes in the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
0
16
0
3
Order By: Relevance
“…The aetiology of miscarriages is multifarious. Previous studies have mainly focused on female factors, including abnormalities of uterine configuration, hormonal and metabolic disorders such as hypothyroidism and diabetes, infections including chronic endometritis, autoimmune abnormalities such as anti‐phospholipid antibody syndrome, thrombophilias, and less commonly, autosomal translocations in either sexual partner (Azumaguchi, Henmi, Ohnishi, Endo, & Saito, ; Garzia et al, ; Kacprzak et al, ). However, approximately 50% of pregnancy losses remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of miscarriages is multifarious. Previous studies have mainly focused on female factors, including abnormalities of uterine configuration, hormonal and metabolic disorders such as hypothyroidism and diabetes, infections including chronic endometritis, autoimmune abnormalities such as anti‐phospholipid antibody syndrome, thrombophilias, and less commonly, autosomal translocations in either sexual partner (Azumaguchi, Henmi, Ohnishi, Endo, & Saito, ; Garzia et al, ; Kacprzak et al, ). However, approximately 50% of pregnancy losses remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that poor pregnancy outcomes are linked to genetic polymorphisms . For example, several polymorphisms of the TNFα gene might have a role in the pathogenesis of RPL.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the classic cytogenetic to assess the fetal karyotype of the miscarriage material is complicated because the sample may be contaminated by the maternal tissue and the associated risk of false negative results. 10 In addition, products of conception are characterized by a low sample quality that often leads to a cell culture failure. 11,12 In case of culture failure or maternal contamination, molecular techniques may contribute to detect additional chromosome abnormalities in these miscarriage samples in addition to standard karyotyping.…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent review also summarized a current knowledge on the genetic causes (karyotype abnormalities, recessive diseases carrier status, dominant diseases and thrombophilia) of the RM. 10 Genetic reasons may involve changes in the genetic embryonic/fetal or parental material. Therefore, genetic tests may be performed in both parents as well as in the miscarriage material (fetus or afterbirth).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation